Pengendalian Kualitas Produk Kardus Menggunakan Metode Statistical Quality Control (SQC) pada CV. XYZ - Mohammad Fachrurrozi Adi; Akhmad Wasiur Rizqi; Deny Andesta (Fakultas Teknik, 2022)
Abstract Quality control is the most important thing in the competition in the industrial world which is of course on packaging products in order to monitor and evaluate production activities to ensure whether they meet the standards set by the company or not. The purpose of this study can help companies to help companies overcome the causes of defects and provide suggestions using the Statistical Quality Control (SQC) method. From the data processing, it was found that the number of production was 162,100 pcs and the number of product defects was 4307 pcs. From the results of the analysis, the authors provide suggestions for improvement by focusing on the most dominant types of defects in the past so that repair activities can run effectively.